Evidence-based practice and intellectual disabilities - Didden, Robert; Sturmey,Peter (Malden, MA : Wiley-Blackwell, 2014)
'Evidence-Based Practice and Intellectual Disabilities responds to the recent increased focus on, and need for, the use of evidence-based practice (EBP) in treating intellectual disabilities. The first book wholly dedicated to addressing EBP specifically in relation to intellectual disabilities Provides clinical guidelines based on the strength of evidence of treatments for a given problematic behavioral topography or disorder Highly relevant to a wide-ranging audience, including professionals working in community services, clinicians and parents and carers'--
'Practice and Intellectual Disabilities will be highly relevant to a wide audience, including professionals working in community services, clinicians working in special education schools, residential facilities, and psychiatric hospitals, and parents and organizations involved in the care of individuals with intellectual disabilities'--
Includes bibliographical references and index.
Keywords: Intellectual Disability -- complications; Intellectual Disability -- psychology; Evidence-Based Practice